Emerging Seafood Preservation Techniques to Extend Freshness and Minimize Vibrio Contamination - Ronholm, Jennifer; Lau, Fiona; Banerjee, Swapan K. (Frontiers in Microbiology, 2016)
Globally, the popularity of seafood consumption is increasing exponentially. To meet the demands of a growing market, the seafood industry has increasingly been innovating ways to keep their products fresh and safe while increasing production. Marine environments harbor several species of indigenous microorganisms, some of which, including Vibrio spp., may be harmful to humans, and all of which are part of the natural microbiota of the seafood. After harvest, seafood products are often shipped over large geographic distances, sometimes for prolonged periods, during which the food must stay fresh and pathogen proliferation must be minimized. Upon arrival there is often a strong desire, arising from both culinary and nutritional considerations, to consume seafood products raw, or minimally cooked. This supply chain along with popular preferences have increased challenges for the seafood industry. This has resulted in a desire to develop methodologies that reduce pathogenic and spoilage organisms in seafood items to comply with regulations and result in minimal changes to the taste, texture, and nutritional content of the final product. This mini-review discusses and compares several emerging technologies, such as treatment with plant derived natural compounds, phage lysis, high-pressure processing, and irradiation for their ability to control pathogenic vibrios, limit the growth of spoilage organisms, and keep the desired organoleptic properties of the seafood product intact.